Neotype designation for Sinonamuropteris ningxiaensis Peng, Hong et Zhang, 2005 (Grylloblattida: Sinonamuropteridae) - Cui, Yingying; Ren, Dong (Zootaxa, 2013)
In contrast to the Permian period, grylloblattidan insects represent a small portion of the Carboniferous entomofaunas (Cui et al. 2011; Béthoux et al. 2010; Storozhenko 2002). The Xiaheyan locality (Tupo Formation; Ningxia, China) is no exception. The nine species of the family Sinonamuropteridae described by Peng et al. (2005) based on material from this locality, and each represented by a single isolated forewing, actually belong to a single species, namely Sinonamuropteris ningxiaensis Peng, Hong et Zhang, 2005 (Cui et al. 2011). To date, this is the only grylloblattidan species from the corresponding fauna, which is dominated by stem-Orthoptera (e.g., Prokop et al. 2007; Gu et al. 2011; Béthoux et al. 2012) and by a few other speciose groups, such as stem-Odonata (e.g., Li et al. 2013).